2021
DOI: 10.1021/acsami.1c07107
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Raspberry-like Cytochrome C Surface-Imprinted Nanoparticles Based on MOF Composites for High-Performance Protein Separation

Abstract: The development of high-performance protein-imprinted materials is vital to meet the requirements of proteomics research but remains a challenge. Herein, a new type of raspberry-like cytochrome C-imprinted nanoparticle was first designed and fabricated via surface imprinting technology combined with a template immobilization strategy. In particular, the state-of-the-art metal–organic framework (MOF)/carbon nanoparticle (CN) composites were selected as protein immobilization carriers for two advantages: (1) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…This may be because the presence of zwitterionic functional groups in MIPs reduces their nonspecific binding. 16,17 Furthermore, the adsorption results for all samples in the binary mixed solution of BSA and Hb were consistent with those in the mixed solution of BSA and Cyt C, except that they had a relatively low α value for template protein, which may be attributed to the similar molecular volume of BSA and Hb. Nonetheless, the α value of SiO 2 @MPS@MIPs-MFM was still higher than 2.0, indicating their excellent rebinding specificity.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…This may be because the presence of zwitterionic functional groups in MIPs reduces their nonspecific binding. 16,17 Furthermore, the adsorption results for all samples in the binary mixed solution of BSA and Hb were consistent with those in the mixed solution of BSA and Cyt C, except that they had a relatively low α value for template protein, which may be attributed to the similar molecular volume of BSA and Hb. Nonetheless, the α value of SiO 2 @MPS@MIPs-MFM was still higher than 2.0, indicating their excellent rebinding specificity.…”
Section: Resultssupporting
confidence: 64%
“…The protein-repelling effect of APBC, such as polyethylene glycol (PEG) and zwitterionic polymers, is achieved by forming a water shell with low free energy at the interface in the aqueous phase. , Taking advantage of this property, Fu et al covered the lysozyme-imprinted layers with slightly crosslinked linear PEG, and protein binding tests showed that the existence of PEG significantly improves their selectivity. Recently, our team incorporated a zwitterionic monomer or a polymer into the preparation process of MIPs, and the prepared MIPs could also achieve efficient separation toward the template protein in a multicomponent protein solution. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Benefiting from the osmotic pressure difference between the inside and outside of the tubular carbon nanofiber, the material exhibited a rebinding capacity of 541.99 mg g −1 and a fast adsorption equilibrium time within 60 min for BSA. Qian et al fabricated raspberry-like surface-imprinted metal-organic framework (MOF) nanoparticles for cytochrome c. Owing to the high specific surface area and unique design, the nanosphere showed an outstanding adsorption capacity for cytochrome c of 815 mg g −1 and an extremely rapid adsorption equilibrium time within 40 min 29 Although the rebinding capacity and selectivity of surface protein-imprinted nanomaterials significantly improved with the development of nanotechnology and design of new nanocarriers, the core of surface imprinted materials (i.e., the polymer layers) has not been widely considered. Most of them are polydopamines or traditional acrylate polymers prepared by random copolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Encouragingly, the resulting MOF@PDA-MIP achieved a significant binding capacity of 313.5 mg g À1 and imprinting factor of 7.8, demonstrating that MOFs are promising materials for the surface imprinting of proteins. Inspired by this study, Qian et al 97 utilized MOFs/carbon nanoparticle (CN) composites (CN@UIO-66) as the substrate to construct the protein surface imprinted polymers. Interestingly, the resulting CN@UIO-66@MIPs possessed a high specific surface area of 551.4 m 2 g À1 , which led to an extremely high binding capacity (815 mg g À1 ) toward Cyt c. Meanwhile, a high imprinting factor of 6.1 and rapid adsorption kinetics of 40 min were obtained.…”
Section: Traditional Imprinting Methodsmentioning
confidence: 99%